Ultrasound Accuracy in Determining the Tumor Depth for Boost Field Radiotherapy in Breast Cancer in Comparison With CT Scan Plus Clips - Barzegar Tahmtan, Mohammad Reza; Aghili, Mahdi; Samiee, Farhad; Haddad, Peyman; Amouzgar Hashemi, Farnaz; Maddah, Afsane; Farhan, Farshid; Alikhasi, Afsane; Omranipour, Ramesh; Nedaee, Hasnali; et al. (Reports of Radiotherapy and Oncology, 2015)
Background: There are miscellaneous methods of boost field determination with different levels of accuracy. One of the important parameters in boost field planning is the tumor bed depth, as it is important for determining electron energy. Objectives: The purpose of present research was the determination of ultrasound accuracy to estimate the appropriate depth for the tumor bed. Patients and Methods: Patients who were undergone breast conservative surgery with placing of 5 clips in the tumor bed (lower, upper, medial, lateral, and posterior) were included. The depth and location of the tumor bed were determined using ultrasonography. The optimum field boost was planned with an appropriate 2.5 cm margin. After putting the marker on the field boost, the CT simulation was done and then the obtained depth of the ultrasound report and that of the CT scan-clips were compared. Results: Twenty five patients were included. The average depth reported by the ultrasound was about 18 mm ± 3 mm (range 10-26 mm), and the average obtained from the CT scan-clips was about 48 mm ± 13 mm (range 24-80 mm), (P Value = 0.001). In almost all cases, the depth obtained from the ultrasound was less than that obtained from the CT scan- clips. Conclusions: Ultrasound is not an accurate method to determine the appropriate depth and field for determination of breast field boost. Thus, it is better not to use ultrasound to estimate the tumor cavity depth; the CT scan images with surgical clips should be used instead.